Economic growth and income distribution: the experience of Indonesia - Jhon Tafbu Ritonga (Penerbit Universiti Kebangsaan Malaysia, 2005)
The economy of Indonesia had come into the social and the political crisis since the second period in 1997. A number of social riots struke several towns in Indonesia. Consequently, the stability of the state was disturbed. It caused the efforts to economy recovery to be more and more difficult to do. Many others pointed out that the social riots were caused by inequality of economy. The purpose of this study is to find out the income inequality stage in Indonesia and wether the good income distribution inequality can ensure the stability of the state. The measurement method for income distribution used in this study is Gini coeficient and World Bank's criteria. The results of the study shows that the economic growth rose significantly during New Order (sociopolitical in Indonesia). While, the income distribution based on Gini Ratio and World Bank's criteria imply that Indonesia is included the category of low inequality. However, in thcstudy's period is found the distortion of Kuznets hypothesis and Ahluwalia's analysis on the change forms of income distribution. The low inequality doesn't reflect to another inequality situation such as poverty and absolute inequality. Therefore, the rising of economic growth and the low inequalit) during the study's period doesn't guarantee the stablity of politic. The studies about the income distribution shouldn't use macroeconomics approach only, but also other approaches like microeconomics aspects.